Comparative evaluation of locally delivered minocycline and metronidazole in the treatment of periodontitis - Nymphea Pandit; Ritu Dahiya; Rajan Gupta; Deepika Bali; Abhinav Kathuria (Wolters Kluwer Medknow Publications, 2013)
Objective: The aim of this study was to evaluate and compare the efficacy of subgingivally delivered Minocycline microspheres and 25% Metronidazole gel when used as an adjunct to scaling and root planing (SRP) in the treatment of chronic periodontitis. Materials and Methods: A randomized, controlled, single center study was conducted involving 60 sites in 20 patients suffering from moderate to advanced chronic periodontitis. Each patient contributed three sites which were randomized to three treatment groups: SRP + insertion of Minocycline microspheres at day 1 (Group A), SRP + insertion of Metronidazole gel at day 1 and at day 7 (Group B), and SRP alone (Group C). Gingival index (GI), plaque index (PI), probing pocket depth (PPD), and clinical attachment level (CAL) were recorded at day 1, 1 month, and 3 months post therapy. Results: All treatments showed significant reductions in PPD and CAL at 1 and 3 months when compared to baseline values ( P < 0.001). At 3 months, sites treated with minocycline showed an additional reduction in PPD of 0.85 ± 0.03 mm, significantly greater than SRP alone. Differences in mean PPD reduction between Group B and Group C and between Group A and Group B were not significant. At 3 months, difference in CAL gain between Group A and C was 0.50 ± 0.45, which was statistically significant and between Group B and C was 0.35 ± 0.11, which was not found to be statistically significant ( P = 0.20). Differences in relative CAL between Group A and Group B were also not found to be statistically significant ( P = 0.53). Conclusion: The results concluded that treatment with Minocycline microspheres and Metronidazole gel improve PPD and CAL in patients with periodontitis compared to SRP alone.